2017
DOI: 10.1016/j.rbmo.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Does elevated progesterone on day of oocyte maturation play a role in the racial disparities in IVF outcomes?

Abstract: The aim of this study was to evaluate if premature progesterone elevation on the last day of assisted reproduction technique stimulation contributes to racial disparities. A total of 3289 assisted reproduction technique cycles were evaluated in Latino, Asian, African American, and white women. Live birth was more likely in white women (42.6%) compared with Asian (34.8%) and African American women (36.3%), but was similar to Latino women (40.7%). In all racial groups, progesterone was negatively associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Contrary to this finding, Hill et al demonstrated that the progesterone to oocyte ratio was not protective, indicating a negative effect regardless of ovarian response [42]. Finally, Hill et al demonstrated that the negative effect of premature P elevation persisted among various ethnicities in a similar fashion, although ethnic minorities had a higher prevalence of premature P elevation [43]. Across all of these studies, interaction testing for live birth by P with each variable was statistically nonsignificant.…”
Section: Is Premature P Elevation Detrimental To All Patients?mentioning
confidence: 92%
“…Contrary to this finding, Hill et al demonstrated that the progesterone to oocyte ratio was not protective, indicating a negative effect regardless of ovarian response [42]. Finally, Hill et al demonstrated that the negative effect of premature P elevation persisted among various ethnicities in a similar fashion, although ethnic minorities had a higher prevalence of premature P elevation [43]. Across all of these studies, interaction testing for live birth by P with each variable was statistically nonsignificant.…”
Section: Is Premature P Elevation Detrimental To All Patients?mentioning
confidence: 92%
“…However, White women were less likely to exhibit this premature elevation in progesterone (progesterone level > 1.5 ng/mL, 10.6%) than Latino women (18.0%) and Asian women (20.2%). The investigators suggest that this reflects the differences in gene or enzyme polymorphisms that result in differential responses to exogenous gonadotropins (41). However, in an earlier study, examining IVF cycles from both White and Asian patients through the national SART registry as well as from an academic medical center, Asian patients were shown to have lower clinical pregnancy rates after adjustment for estradiol level on the day of trigger and endometrial thickness despite demonstrating significantly decreased embryo fragmentation scores compared with White women (aOR, 0.59; 95% CI, 0.37-0.94) (42).…”
Section: Disparities In Outcomes Of Infertility Treatmentmentioning
confidence: 99%
“…Excessive P levels may affect the embryo quality and endometrial receptivity, reduce the embryo implantation rate, and thus reduce the clinical pregnancy rate [ 4 ]. Earlier studies did not show any association between P levels and pregnancy rates [ 5 , 6 ], whereas more recent studies have reported a negative impact on pregnancy outcomes when serum P levels are increased [ 4 , 7 ]. In this case, which indicator can we choose to predict pregnancy outcomes and subsequently decide to perform fresh embryo transfer (ET) or the “freeze-all” strategy?…”
Section: Introductionmentioning
confidence: 99%